O professor-ator ou o jogo da sedução na relação professor-aluno - Nassar, Sergio Pessoa (1993)
For such a long time we have known a great variety of actors: from cinema, from TV, from theatre, from circus ... Other wise there is another one to whom people does not pay attention: the human being. This kind of actor supports a lot of characters for all his life. One of them is the teacher. The teacher-actor, as I call him, represents for a peculiar audience - the students - with an special purpose seduce them for they have exit in teaching and learning process. This study shows us contributions from the teacher - actor to the educative process. It also emphasizes the kind of relationship between teacher and student from their points of view. It is a phenomenological approach about relationship between teacher and student and its consequences for teaching and learning process.